Inovasi Pembelajaran Menulis Cerpen melalui Context Teaching Problem Learning (CTPL) pada Siswa Kelas XII Madrasah Aliyah - Jannah, Kamilatul; Alatas, Mochamad Arifin (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
Writing short stories in secondary education is often procedural and lacks connection to students’ real-life contexts. This study aims to explore the application of Context Teaching Problem Learning (CTPL) in teaching short story writing to 12th-grade students at MA Al-Azhar. CTPL integrates Contextual Teaching and Learning (CTL) and Problem-Based Learning (PBL), emphasizing real-life experiences and social issues as the foundation for writing. A qualitative approach with a case study design was employed, using observation, in-depth interviews, and documentation for data collection. The data were analyzed using interactive analysis techniques, including data reduction, data display, and conclusion drawing. The findings reveal that CTPL encourages students to write short stories rooted in personal experiences and social concerns, enhancing creativity, empathy, and social awareness. Teachers act as facilitators to guide reflective and meaningful learning. The students’ stories not only meet literary criteria but also convey life values. CTPL successfully fosters an inclusive and humanistic learning environment, supporting the development of students' expressive, narrative, and character-building skills.Penulisan cerpen di jenjang pendidikan menengah sering kali bersifat prosedural dan kurang menyentuh konteks kehidupan siswa. Penelitian ini bertujuan untuk mengeksplorasi pembelajaran menulis cerpen dengan pendekatan Context Teaching Problem Learning (CTPL) pada siswa kelas XII MA Al-Azhar. CTPL merupakan integrasi antara Contextual Teaching and Learning (CTL) dan Problem-Based Learning (PBL), yang menempatkan pengalaman nyata dan permasalahan sosial sebagai landasan dalam proses menulis. Penelitian ini menggunakan pendekatan kualitatif dengan desain studi kasus. Data dikumpulkan melalui observasi, wawancara mendalam, dan dokumentasi. Teknik analisis data yang digunakan adalah analisis interaktif yang mencakup reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa pendekatan CTPL mendorong siswa untuk menulis cerpen berdasarkan pengalaman personal dan isu sosial di sekitar mereka, sehingga meningkatkan kreativitas, empati, serta kesadaran sosial. Guru berperan sebagai fasilitator dalam menciptakan pembelajaran yang reflektif dan bermakna. Cerpen yang dihasilkan siswa tidak hanya memenuhi unsur sastra, tetapi juga sarat nilai-nilai kehidupan. CTPL terbukti mampu membangun suasana belajar yang inklusif dan humanis, serta memfasilitasi pertumbuhan kemampuan ekspresif, naratif, dan karakter siswa secara menyeluruh.